UTILIZAÇÃO DE RESÍDUOS ORIUNDOS DA INDÚSTRIA CALÇADISTA DE FRANCA/SP NA CONFECÇÃO DE BLOCOS DE VEDAÇÃO - Silva, Fabiana Andresa da; Baldan, Victor José dos Santos; Pablos, Javier Mazariegos; Murari, Alexandre Rodriguez; Sichieri, Eduvaldo Paulo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The leather tanning and shoe manufacturing industries generate a large volume of solid waste with different characteristics, due to the presence of various materials in the tanning process. In this way, these wastes must be managed properly to avoid environmental pollution as well as damage to human health. The maximum use of this process is necessary before the waste is discarded, for example by recycling such waste. Therefore, this research aims to develop sealing blocks from the incorporation of the footwear industries of the city of Franca / SP and verify their application in civil construction. For this, the residue was duly ground and classified according to the Brazilian standardization. Subsequently, it was possible by pressing to make a sealing block from the incorporation of the leather residue into the starch binder. The results obtained through the mechanical properties tests showed that these blocks can be used by the civil construction industry as a sealing element. Therefore, it is expected that this research contributes to the minimization of the final destination of waste from the leather-footwear industry.